Career patterns of young highly skilled migrants from Southeast Europe in Austria: Investigating accumulation and use of career capital. Issue 2 (6th March 2017) - Winterheller, Julian; Hirt, Christian
Abstract : Purpose: Using a Bourdieuian perspective, the purpose of this paper is to analyse how highly skilled migrants (HSMs) from transition economies develop their careers by accumulating and using career capital upon migration. Design/methodology/approach: An interpretative approach was chosen to depict the career patterns of 18 HSMs from Southeast Europe. Semi-structured interviews were used to gather data about their career experiences in Western Europe and their home countries. Findings: Findings reveal four different career patterns that show how individuals develop their careers and adjust to the work environment by accumulating and using career capital. Building up country-specific work-related social contacts and gaining work experience in local companies were found to represent key elements in their adjustment process. Additionally, the findings show that organisational support facilitates the processes of individual adjustment. Originality/value: This paper emphasises that individuals do not always have to assimilate to the work environment of the host country but can also bargain over the value of their career capital in their adjustment process. Contrasting with previous literature this perspective presents a novelty.